PENGARUH QUANTUM TEACHING PERMAINAN RANGKING SATU TERHADAP HASIL BELAJAR ASAM BASA SMK - Tresna Kurniawati; Eny Enawati; Masriani Masriani (Universitas Muhammadiyah Pontianak, 2020)
This study aims to determine differences in learning outcomes and influence teaching and learning quantum learning with rangking one game on learning outcomes. The form of research used was quasi-experimental design with random sampling techniques. The sample of this researche is class X TKJ A as an experimental class that gathers 28 students and X TKJ B as a control class againts 26 students. Data calculation techniques are measurement and interview techniques. Based on the analysis using the U-Mann Whitney test ( which shows the differences in learning utcomes between students who use quantum learning teaching with the first rank game using conventionals models. Quantum learning teaching with this one rangking game gives a high influence on learning outcomes with an effect size value of 1,5